Take the 2-minute tour ×
MathOverflow is a question and answer site for professional mathematicians. It's 100% free, no registration required.

It is very easy to show that the series $$\frac{1-1/2}{1\times2} - \frac{1-1/2+1/3}{2\times3} + \frac{1-1/2+1/3-1/4}{3\times4} - ...$$ i.e. $$\sum_{n=1}^{\infty} \frac{(-1)^{n+1}}{n(n+1)}[1-\frac{1}{2} + \frac{1}{3} - ...+ \frac {(-1)^{n}}{n+1}]$$ is convergent. Can one find its exact value? Or is it unreasonable to hope for such a thing? Thank you for your answers.

share|improve this question
    
The first thing that came to mind is that you might need Cesaro summability or something (cf. exercise 12-37 in Apostol, Mathematical Analysis), but I'm not sure that gets you where you where you want to go. It seems reasonable that this might be possible. Have you tried Hardy's Divergent Series? There may be a simple answer (one way or the other), but I'm not seeing it. –  Chris Leary Sep 14 '11 at 17:24
add comment

2 Answers 2

The interior sum is equal to $\int_0^1\frac{1-(-x)^{n+1}}{1+x}dx$ and $$ \sum _{n=1}^{\infty } \frac{(-1)^{n+1} \left(1-(-x)^{n+1}\right)}{n (n+1) (x+1)}= \frac{(x-1) \log (1-x)-x+\log (4)-1}{1+x}. $$ So the answer is eqaul to $$ \int_0^1 \frac{(x-1) \log (1-x)-x+\log (4)-1}{1+x}dx=\frac{\pi ^2}{6}+\log ^2(2)-2. $$

share|improve this answer
    
What do you mean by interior sum? –  Michael Albanese Sep 4 '12 at 10:24
add comment

Since

$$\frac1{n(n+1)}=\frac1n-\frac1{n+1},$$

we have

$$\begin{aligned} \sum_{n=1}^N\sum_{k=1}^{n+1}\frac{(-1)^{n+k}}{kn(n+1)} &=\sum_{n=1}^N\sum_{k=1}^{n+1}\frac{(-1)^{n+k}}{kn}+\sum_{n=2}^{N+1}\sum_{k=1}^n\frac{(-1)^{n+k}}{kn}\\\\ &=2\sum_{n=1}^N\sum_{k=1}^n\frac{(-1)^{n+k}}{kn}-\sum_{n=1}^N\frac1{n(n+1)}-1+\sum_{k=1}^{N+1}\frac{(-1)^{N+1+k}}{k(N+1)}\\\\ &=\sum_{n,k=1}^N\frac{(-1)^{n+k}}{kn}+\sum_{n=1}^N\frac1{n^2}-2+\frac1{N+1}+\frac{(-1)^{N+1}}{N+1}\sum_{k=1}^{N+1}\frac{(-1)^k}k\\\\ &=\left(\sum_{n=1}^N\frac{(-1)^{n}}n\right)^2+\sum_{n=1}^N\frac1{n^2}-2+\frac1{N+1}+\frac{(-1)^{N+1}}{N+1}\sum_{k=1}^{N+1}\frac{(-1)^k}k. \end{aligned}$$

As $\sum_{n=1}^\infty\frac{(-1)^n}n=-\log2$ and $\sum_{n=1}^\infty\frac1{n^2}=\frac{\pi^2}6$, this implies

$$\sum_{n=1}^\infty\frac{(-1)^{n+1}}{n(n+1)}\sum_{k=1}^{n+1}\frac{(-1)^{k+1}}k=(\log2)^2+\frac{\pi^2}6-2.$$

There may be a numerical error somewhere, but in principle the method should work.

share|improve this answer
    
I did not check, but may this sum be negative a priori? –  Fedor Petrov Sep 14 '11 at 18:12
    
Thanks, fixed. –  Emil Jeřábek Sep 14 '11 at 18:18
    
This can't be right as stated because it's negative. But your method must work because I get $(\log 2)^2 + \pi^2/6 - 2$ by a different approach. –  Noam D. Elkies Sep 14 '11 at 18:34
    
...which I see that Andrew just posted. –  Noam D. Elkies Sep 14 '11 at 18:35
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.